Darwinism as religion : what literature tells us about evolution - Ruse, Michael (Oxford University Press, 2017)
'Darwinism as Religion' argues that the theory of evolution given by Charles Darwin in the nineteenth century has always functioned as much as a secular form of religion as anything purely scientific. Through the words of novelists and poets, Michael Ruse argues that Darwin took us from the secure world of Christian faith into a darker, less friendly world of chance and lack of meaning.